2009
DOI: 10.3354/meps08001
|View full text |Cite
|
Sign up to set email alerts
|

High connectivity of salmon farms revealed by aggregation, residence and repeated movements of wild fish among farms

Abstract: Marine fish farms are widespread in coastal waters throughout the world, yet how they modify the movement patterns of wild fish species is largely unknown. We determined the spatiotemporal distribution of saithe Pollachius virens in a fjord system with intensive salmon cage aquaculture in Norway. Abundances of 8000 to 18 000 saithe were estimated around 2 salmon farms in the fjord using an underwater video system. Residence of saithe around fish farms and movements among farms and throughout the fjord were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 29 publications
1
103
0
1
Order By: Relevance
“…These characteristics of the marine environment likely underlie the observation that diseases spread at rates an order of magnitude faster in the oceans than they do on land (McCallum et al 2003). These characteristics, in addition to connectivity of farms by wild fish movement (Uglem et al 2009), suggest that the spatial scale for host density thresholds in the oceans is likely larger than an individual farm and likely occur at regional scales such as large embayments, fjords, or archipelagos.…”
Section: Empirical Evidence For Thresholdsmentioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics of the marine environment likely underlie the observation that diseases spread at rates an order of magnitude faster in the oceans than they do on land (McCallum et al 2003). These characteristics, in addition to connectivity of farms by wild fish movement (Uglem et al 2009), suggest that the spatial scale for host density thresholds in the oceans is likely larger than an individual farm and likely occur at regional scales such as large embayments, fjords, or archipelagos.…”
Section: Empirical Evidence For Thresholdsmentioning
confidence: 99%
“…Infection pressure, however, likely declines rapidly with distance from source population. In addition, microparasites may spread among farms over broad spatial scales due to the movement of wild fish populations (Uglem et al 2009). For example, herpes epidemics of Australian pilchard stocks in 1995 and 1998-1999 spread at rates of 30 km d -1 or 10 000 km yr -1 (Jones et al 1997, Gaughan et al 2000, McCallum et al 2003.…”
Section: Empirical Evidence For Thresholdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimates assume that fish outside this limited area are not farm-associated, which is unlikely to be the case for mobile pelagic species such as Pollachius virens and S. scombrus. Ultrasonic tagging and tracking of farm-associated P. virens in Øksfjord revealed that P. virens may be resident at farms for weeks to months or may move among different farms and natural locations several kilometers apart (Uglem et al 2009), thus using farms as frequently visited locations within a wider home range. If P. virens regularly move in and out of the attractive area of farms, this process would mask the true numbers of P. virens that regularly interact with farms, which are likely to be higher than our estimates restricted to the area of the cages.…”
Section: Abundance and Biomass Estimates From Video Countsmentioning
confidence: 99%
“…Aggregation of wild fish adjacent to caged fish may also increase the risk of transfer of shared pathogens between the 2 groups (Diamant et al 2007, Uglem et al 2008 or, possibly, to nearby fish farms if wild fish migrate between farms (Uglem et al 2009). The concentration of wild fish at fish farms may assist in nutrient dispersal at farming sites (Vita et al 2004) and could also increase the vulnerability of fish to capture, which has led to the proposed implementation of nofishing zones around sea-cage farms .…”
Section: Introductionmentioning
confidence: 99%